Deleuze and Guattari's a thousand plateaus a critical introduction and guide - Adkins, Brent 1969- (Edinburgh Edinburgh University Press, 2015)
Brent Adkins demonstrates that all the questions raised by A Thousand Plateaus are in service to Deleuze and Guattari's radical reconstruction of the methods and aims of philosophy itself. This book will appeal to teachers of the text or anyone wanting to engage with it at a deeper level -- Cover
Introduction: a perceptual semiotics -- Rhizome -- 1914: one or several wolves? -- 10,000 BC: the geology of morals -- November 20, 1923: postulates of linguistics -- 587 BC-AD 70: on several regimes of signs -- November 28, 1947: how do you make yourself a body without organs? -- Year zero: faciality -- 1874: three novellas, or "what happened?" -- 1933: micropolitics and segmentarity -- 1730: becoming-intense, becoming-animal, becoming-imperceptible... -- 1837: of the refrain -- 1227: treatise on nomadology-the war machine -- 7000 BC: apparatus of capture -- 1440: the smooth and the striated -- Conclusion: the ethics of becoming -- Suggestions for further reading -- Bibliography -- Index
Includes bibliographical references (pages 254-259) and index.
Keywords: Deleuze, Gilles -- 1925-1995.; Guattari, Fâelix -- 1930-1992.; Philosophy; Psychoanalysis; Radicalism; Postmodernism